Find the power series solution of the differential equation
𝑦``+𝑥𝑦`+(𝑥2+2)𝑦=0
Solution
Let
"y\\left(x\\right)=\\sum_{n=0}^{\\infty}{a_nx^n}"
"\\frac{dy}{dx}=\\sum_{n=1}^{\\infty}{na_nx^{n-1}}=\\sum_{n=0}^{\\infty}{\\left(n+1\\right)a_{n+1}x^n}"
"\\frac{d^2y}{dx^2}=\\sum_{n=0}^{\\infty}{n\\left(n+1\\right)a_{n+1}x^{n-1}}=\\sum_{n=0}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}x^n}"
Substitution into equation:
"\\sum_{n=0}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}x^n}+\\sum_{n=0}^{\\infty}{\\left(n+1\\right)a_{n+1}x^{n+1}}+\\sum_{n=0}^{\\infty}{a_nx^{n+2}}+2\\sum_{n=0}^{\\infty}{a_nx^n}=0"
"\\sum_{n=0}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}x^n}+\\sum_{n=1}^{\\infty}{na_nx^n}+\\sum_{n=2}^{\\infty}{a_{n-2}x^n}+2\\sum_{n=0}^{\\infty}{a_nx^n}=0"
"2a_2+6a_3x+2a_0+3a_1x+\\sum_{n=2}^{\\infty}{\\left(n+1\\right)\\left(n+2\\right)a_{n+2}x^n}+\\sum_{n=2}^{\\infty}{na_nx^n}+\\sum_{n=2}^{\\infty}{a_{n-2}x^n}+2\\sum_{n=2}^{\\infty}{a_nx^n}=0"
Coefficient near xn are equal to zero.
n=0: 2a2 + 2a0=0 => a2 = -a0
n=1: 6a3+3a1=0 => a3=-a1 /2
n>1: (n+1)(n+2)an+2+nan+an-2+2an=0 => (n+1)(n+2)an+2+(n+2)an+an-2=0
an+2 =-an/(n+1)-an-2/[(n+1) (n+2)]
Therefore for arbitrary a0 and a1 and last recurrent formula solution is
"y\\left(x\\right)=a_0+a_1x\\ -a_0x^2-\\frac{a_1}{2}x^3+\\sum_{n=2}^{\\infty}{a_{n+2}x^{n+2}}"
Comments
Leave a comment